Proprotein convertase subtilisin/kexin type 9 (PCSK9): From structure-function relation to therapeutic inhibition - Tibolla, G.; Norata, Giuseppe; Artali, R.; Meneghetti, F.; Catapano, A. (Elsevier, 2011)
Aims: This short review aims at summarizing the current information on Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) structure and function focusing also on the therapeutic possibilities based on the inhibition of this protein. Data synthesis: PCSK9 has been recently discovered as the third gene involved in autosomal dominant hypercholesterolemia. PCSK9 binds and favors degradation of the low-density lipoprotein receptor (LDLR) and thereby modulates the plasma levels of LDL-cholesterol (LDL-C). Some of the natural occurring PCSK9 mutations increase the protein function (gain of function) and cause hypercholesterolemia, whereas loss of function mutations associate with hypocholesterolemia. Since the loss of a functional PCSK9 in humans is not associated with apparent deleterious effects, this protease is an attractive target for the development of lowering plasma LDL-C agents, either alone or in combination with statins. Conclusion: Inhibition of PCSK9 is emerging as a novel strategy for the treatment of hypercholesterolemia and data obtained from pre-clinical studies show that use of monoclonal antibodies, antisense oligonucleotides and short interfering RNA are effective in reducing LDL-C, clinical studies, accompanied by a better understanding of PCSK9 biology, are now necessary to address whether these new compounds will have a future in clinical practice. © 2011 Elsevier B.V.